2008
DOI: 10.1123/jpah.5.s1.s183
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Examination of the Most Frequently Used Activity Settings in 25 Community Parks Using Direct Observation

Abstract: Paved trails were only in 5 of the 25 parks but were the most frequently used activity setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 21 publications
7
44
1
1
Order By: Relevance
“…In this review, we included 34 articles representing 24 distinct studies (Table 1). However, in one case we presented an earlier study that reported only on adults (Reed et al, 2008) as well as the extension of the study that reported only on youth (Reed and Hooker, 2012). The earliest study initiated observations in 2003 (McKenzie et al, 2006), when the SOPARC method was created, and the latest study started observations in 2013 (Roemmich and Johnson, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we included 34 articles representing 24 distinct studies (Table 1). However, in one case we presented an earlier study that reported only on adults (Reed et al, 2008) as well as the extension of the study that reported only on youth (Reed and Hooker, 2012). The earliest study initiated observations in 2003 (McKenzie et al, 2006), when the SOPARC method was created, and the latest study started observations in 2013 (Roemmich and Johnson, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of park users, one study reported observing adults only (Reed et al, 2008) and two reported observing youths only (Coughenour et al, 2014; Floyd et al, 2011; Reed and Hooker, 2012). Several other studies modified the age categories by combining teenagers with adults (< = 12 years and > = 13 years) (Chung-Do et al, 2011; Floyd et al, 2008a) and two studies combined all youths, not distinguishing younger and older youths (Child et al, 2014; McCormack et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice to engage in physical activity at a park rather than to be sedentary is likely associated with several factors including sex, age, access to the park, and the amenities available at the park (10). The presence of certain park amenities such as playgrounds, sport courts, and paths seem to promote physical activity among park users (1113). However, evidence regarding the most and least used amenities is inconsistent (1214).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, park-based physical activity is studied through observation during summer (13,15,16) and, occasionally, spring in warm climates (12). However, weather conditions probably influence park visitation and amenity use, even during the warm-weather seasons of spring and summer.…”
Section: Introductionmentioning
confidence: 99%